Pengaruh Tingkat Suku Bunga, Tingkat Bagi Hasil, Financing To Deposit Ratio, dan Pembiayaan Mudharabah di Bank Umum Syariah - Lisa Hanifah; Saiful Anwar (ITB Ahmad Dahlan Jakarta, 2020)
This study aims to determine the analysis of the influence of the Interest Rate, Profit Sharing Rate, and Financing to Deposit Ratio on Mudharabah Financing at Islamic Commercial Banks in Indonesia. The problem is still low Distribution of mudharabah financing, and financing in Islamic banks dominated by Murabaha financing is a global phenomenon. Mudharabah financing should be the main product in Islamic banks. This type of research is a quantitative descriptive. The population of this study is all Sharia Commercial Bank financial reports in Indonesia, and the sample of this study is the annual financial report (annual report) of Sharia Commercial Bank as many as 33 samples with a sampling technique using a purposive sampling method. Analysis of the data used is multiple linear regression analysis. The results of the study indicate that the interest rate variable does not affect mudharabah financing, evidenced by t count of -0.233 <t table of 2.042 and a probability value of (0.517> 0.05). The level of profit-sharing has a positive and significant effect on Mudharabah Financing can be proven (t count 3.437> t table 2.042); the significance is less than 0.05 (0.002 <0.05). Financing to Deposit Ratio affects mudharabah financing can be proven (t count -2.498> t table 2.042), the significance is less than 0.05 (0.018 <0.05).